2016
DOI: 10.1109/tmi.2015.2463723
|View full text |Cite
|
Sign up to set email alerts
|

Transport on Riemannian Manifold for Connectivity-Based Brain Decoding

Abstract: Abstract-There is a recent interest in using functional magnetic resonance imaging (fMRI) for decoding more naturalistic, cognitive states, in which subjects perform various tasks in a continuous, self-directed manner. In this setting, the set of brain volumes over the entire task duration is usually taken as a single sample with connectivity estimates, such as Pearson's correlation, employed as features. Since covariance matrices live on the positive semidefinite cone, their elements are inherently inter-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…To do so, Riemannian space is approximated with an associated tangent space and then functional connectivity estimates are mapped to the tangent space. We have reported in this paper that this tangent space parameterization results in a significant increase in predictive power of functional connectivity estimates, as previously shown in [83,84]. Our results have also demonstrated that additional shrinkage is not necessarily required on well regularized connectivity estimates in tangent space; however, could be applied for noiser data.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…To do so, Riemannian space is approximated with an associated tangent space and then functional connectivity estimates are mapped to the tangent space. We have reported in this paper that this tangent space parameterization results in a significant increase in predictive power of functional connectivity estimates, as previously shown in [83,84]. Our results have also demonstrated that additional shrinkage is not necessarily required on well regularized connectivity estimates in tangent space; however, could be applied for noiser data.…”
Section: Resultssupporting
confidence: 76%
“…In terms of step-1 (brain parcellation), we compared sICA with MODL, and found that the performance of these is similar (although sICA outperforms for age prediction, as shown in Figure A.34). Lastly, we compared ICA 50D with YEO higher dimensional parcellation (200D and 400D) on HCP data, and found that low dimensional sICA still outperforms higher dimensional YEO parcellation (as shown in Comparison with Literature: Somewhat similar evaluations of various methods (in this problem domain) have previously been carried out in [83,84]. In [83], authors proposed that matrix whitening transform and parallel transport could be utilized to project covariance matrices into a common tangent space and evaluated this method on twenty four healthy subjects.…”
Section: Results External Evaluationmentioning
confidence: 71%
See 2 more Smart Citations
“…While, Chen et al 18 enhanced NBS regulating the topological structures comprised. Other research groups [19][20][21] leveraged support vector machines (SVM) weights to identify discriminating regions. SVM is a supervised learning method which constructs a hyperplane or set of hyperplanes in a high-or infinite-dimensional space used for classification.…”
Section: Local Differences Between Connectomesmentioning
confidence: 99%